Etching (Northbrook, Ill. Roland Collection, 1992)
Demonstrates a number of basic etching techniques, showing the creating of an etching from initial drawing through final printing.
VHS format.
Director, Gavin Nettleton ; writers / consultants, Gavin Nettleton and Terry Gravett.
Narrator, Barbara Myers.
Keywords: Etching -- Technique